The Comparison of Curriculum in Elementary Education between Indonesia and Singapore - Efendi, Moch. Yusuf; Lien, His Nancy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
Indonesia and Singapore, despite having very different approaches to basic education, both perform highly in standardized testing and are respected internationally for their education systems. However, there are many obstacles that should be solved and evaluated so as to provide a solid foundation for students to pursue higher education. Based on this reality, a curriculum comparison needs to be done with countries that already have the best quality education system in this regard Singapore. The objective of the paper is to obtain a summary of the comparison of the curriculum development between Indonesia and Singapore. Indonesia has made several changes in its educational curriculum. The method used is to use a comparative method with a literature review. Indonesia always in low position in international assessment although many things are done to improve the rank of Indonesia. PISA 2015 results positioned Indonesian students in the lowest order. On the contrary, many countries in Southeast Asia are in the top position, such as Singapore which has the best position in Southeast Asia and even on the world level, Singapore is in the top position compared to Indonesia lower than PISA 2015 result shows that the dominance of countries in East Asia. From this study, there are several findings can be adopted in the curriculum of primary schools in Indonesia such as: 1) The application of a uniform curriculum in each school, 2) The function of teachers in preparing their students graduation and 3) The use of instructional media and emphasis on mastery of learning materials. The advantages of this study are: 1) The school can apply the curriculum from the government without ignoring local wisdom, 2) The teachers are able to prepare the students` preparation earlier, and 3) The teachers can prepare them self to be skill full in operating Information Communication and Technology (ICT) devices.